Princípio do contraditório - do estado liberal ao estado democrático de direito - Bersot, Karin Loize Holler Mussi (Universidade do Vale do Rio dos Sinos, 2011)
This research approaches the Principle of Contradictory and in analyzing it during the period from the Liberal State to the Democratic State of Law, aims to base a discussion regarding a civil process model that is suited to Democratic State of Law. Through exposure the historical evolution of theories about the process and the contradictory, passes through the three paradigms of the Law History: the Liberal State, Social State and Democratic State. The research problem is how to form civil proceedings committed to the paradigmatic foundations of this Democratic State of Law. The overall goal is analyze the main currents of civil procedure thought, focusing on how they accomplished the contradictory from the procedural liberalism and the socialization of the case, as well as trace the possibility conditions so that the process be committed to the paradigm of Democratic State of Law. The methodology used is the literature research and approach method is the phenomenologicalhermeneutic, considering the historical context in which the events occurred. The procedure method is historical because comes to aspects of civil procedure, with emphasis on the contradictory, since the Liberal State to the legal culture of today. As a result, we have that to obtain the social transformation desired by Democratic State of Law, the application and interpretation of legal standard, according to the 1988 Constitution, should be conducted in respect of Constitutional principles, especially the principle of Contradictory. This research concludes that to the Principle of Contradictory be fully achieved, it’s necessary that the judge listen the citizen, guaranteeing an exercise of the right of defense much wider than a mere formality to be fulfilled. The contradictory must be faced as an essential aid institute in approaching the case with the material truth and consequently the righteous decision in the specific case, requiring a constant dialogue between all involved in the process, which should be in a similar hierarchical position, being fully achieved in ordainment, to its social efficiency, obtained by direct participation of all subjects in the process.
Keywords: Princípio do contraditório; Estado democrático de direito; Hermenêutica jurídica; Estado juiz; Principle of contradictory; Democratic state of law; Legal hermeneutics; State judge; ACCNPQ::Ciências Sociais Aplicadas::Direito